2023
DOI: 10.1101/2023.03.16.532850
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Group 2 innate lymphoid cells promote inhibitory synapse development and social behavior

Abstract: The innate immune system plays essential roles in brain synaptic development, and immune dysregulation is implicated in neurodevelopmental diseases. Here we show that a subset of innate lymphocytes (group 2 innate lymphoid cells, ILC2s) is required for cortical inhibitory synapse maturation and adult social behavior. ILC2s expanded in the developing meninges and produced a surge of their canonical cytokine Interleukin-13 (IL-13) between postnatal days 5-15. Loss of ILC2s decreased cortical inhibitory synapse n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Both IL-4 and its receptors are expressed in the brain in neurons, oligodendroglia, astrocytes and microglia, and IL-4R expression increases after ischemic stroke indicative of a neuroprotective role (Amo-Aparicio et al, 2021; Bozinov et al, 2008; Fenn, Henry, Huang, Dugan, & Godbout, 2012; Lee, Koh, Lo, & Marchuk, 2018; T. F. Liu et al, 2003). About 25 % of neurons express IL-4RA, and an essential role of IL-4/IL-13 in the formation of inhibitory cortical synapses for normal social behavior is emerging for which a postsynaptic location of IL-4RA and IL-13RA1 is anticipated (Barron et al, 2023). In models of CNS injury, IL-4 protects neurons and induces recovery of injured neurons through neuronal IL-4RA (Walsh et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Both IL-4 and its receptors are expressed in the brain in neurons, oligodendroglia, astrocytes and microglia, and IL-4R expression increases after ischemic stroke indicative of a neuroprotective role (Amo-Aparicio et al, 2021; Bozinov et al, 2008; Fenn, Henry, Huang, Dugan, & Godbout, 2012; Lee, Koh, Lo, & Marchuk, 2018; T. F. Liu et al, 2003). About 25 % of neurons express IL-4RA, and an essential role of IL-4/IL-13 in the formation of inhibitory cortical synapses for normal social behavior is emerging for which a postsynaptic location of IL-4RA and IL-13RA1 is anticipated (Barron et al, 2023). In models of CNS injury, IL-4 protects neurons and induces recovery of injured neurons through neuronal IL-4RA (Walsh et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Although the basis for the difference between lung and meningeal ILC2s is unclear, lung ILC2s are exposed to far more environmental stimuli than meningeal ILC2s, likely leading to these transcriptional differences. A recent study reported that during development, meningeal ILC2s are required for cortical inhibitory synapse maturation and adult social behavior ( Barron et al, 2023 ). This function of ILC2 seems to be dependent on IL-13-production.…”
Section: Innate Lymphoid Cells In the Cnsmentioning
confidence: 99%
“…The release of IFN-γ by T lymphocytes is also implicated in synaptic elimination by microglia and cognitive sequelae, as illustrated by spatial learning deficits in an animal model of flavivirus infection [78]. Also, a subset of innate lymphocytes is involved in cortical inhibitory synapse formation with impacts on social behavior development [79]. This may have important implications in the recent context of COVID-19, where the mechanisms associated with the long-term cognitive sequelae of Long COVID are still under investigation.…”
Section: Microglial and Neuroplasticity: Impact On Neurological Outco...mentioning
confidence: 99%